Climatic drivers of trait assembly in woody plants in Japan. (15th April 2015) - Shiono, Takayuki; Kusumoto, Buntarou; Maeshiro, Ryo; Fujii, Shin‐Jiro; Götzenberger, Lars; de Bello, Francesco; Kubota, Yasuhiro; Linder, Peter
Abstract Aim A trait‐based biogeographical approach can be used to shed light on species‐sorting mechanisms that are driven by the interactions between species traits and abiotic conditions along large‐scale gradients. We tested the hypothesis that geographical patterns of woody plant assemblages are driven largely by environmental filtering, in relation to climate harshness and seasonality, acting on key functional traits. Location Japanese archipelago. Methods Using a large‐scale grid‐based dataset of 773 woody species and five functional traits measured in the field, spanning the Japanese archipelago, we analysed the influence of climate harshness (absolute minimum temperature and precipitation of driest month) and climate seasonality (temperature and precipitation seasonality, and the length of period suitable for photosynthesis) on three aspects of community trait structure: community mean trait values, functional richness and functional divergence. To confirm whether the influence of climate‐based species sorting on functional structure was stronger than the impact of dispersal limitation, we used null models that did or did not account for the difference in regional species pools as a result of vicariance. Results While climate harshness and historical dispersal limitation had a some influence on trait structure, temperature seasonality played a significant role. Greater seasonality was associated with functional similarity in wood density and leaf nitrogen concentration, but also contributed to increased diversity in leaf thickness, specific leaf area and maximum height. Main conclusions Our results demonstrate the importance of climate harshness and seasonality in shaping the geographical variation of functional trait structures in woody plant assemblages, while we found that species richness decreases with increasing climate harshness. Climate seasonality results in the convergence and divergence of co‐occurring traits across different vegetation zones. This suggests that seasonal environmental variability acts not only as a filter of species traits but also as a driver creating a greater difference in functional strategies among woody plant species.